2022
DOI: 10.3389/fvets.2022.946447
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Gene Co-expression Network Analysis Revealed That CircMARK3 Is a Potential CircRNA Affects Fat Deposition in Buffalo

Abstract: BackgroundBuffalo meat is increasingly widely accepted for consumption as it shares several quality attributes with cattle meat (beef). Hence, there is a huge opportunity for growth in the buffalo meat industry. However, buffalo meat has relatively low intramuscular fat (IMF) content, affecting its flavor, tenderness and juiciness. As there is a dearth of information on factors that control fat deposition, this study was undertaken to provide new candidate factor associated with buffalo fat deposition. Circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The binding of plasma triglyceride fatty acids to white adipose tissue is LPL-dependent and the enzyme is regulated by angiopoietin-like protein-4 (ANGPTL-4), an unfolding molecular chaperone that converts active LPL dimers to inactive monomers [ 41 ]. Feng et al [ 24 ] reported that circMARK3 promoted the adipogenic differentiation of buffalo adipocytes and 3T3-L1 cells by up-regulating the expression levels of lipogenic marker genes PPARγ , C/EBPα , and FABP4 . FABP4 is involved in fatty acid transport and plays an important role in animal fat deposition [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of plasma triglyceride fatty acids to white adipose tissue is LPL-dependent and the enzyme is regulated by angiopoietin-like protein-4 (ANGPTL-4), an unfolding molecular chaperone that converts active LPL dimers to inactive monomers [ 41 ]. Feng et al [ 24 ] reported that circMARK3 promoted the adipogenic differentiation of buffalo adipocytes and 3T3-L1 cells by up-regulating the expression levels of lipogenic marker genes PPARγ , C/EBPα , and FABP4 . FABP4 is involved in fatty acid transport and plays an important role in animal fat deposition [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA binds miRNAs through a sponge, preventing miRNAs from bindings to their target genes to regulate mRNA expression by blocking their binding [ 21 ]. For instance, circSAMD4A promotes the differentiation of preadipocytes by acting as an miR-138-5p sponge in humans [ 22 ], while the sus_circPAPPA2 inhibited the fat deposition of ovariectomized pigs through the miR-2366/glycoprotein k (GK) pathway [ 23 , 24 ]. The circRNA/miRNA interaction reveals a new epigenetic regulatory layer.…”
Section: Introductionmentioning
confidence: 99%
“…The highest expression levels of circ‐0001122 and circ‐007367 are found in the bovine mammary gland, but they differ in other tissues (Feng, Cai, et al, 2022). The expression of circMARK3 in fat is higher than that of other tissues, and it aids in the differentiation of bovine adipocytes (Feng, Zhao, et al, 2022). The circTCF4 is expressed at a level that is highest in the gastrocnemius, followed by skeletal muscle, and at a level that is lowest in the liver.…”
Section: Basic Knowledge Of Circrnasmentioning
confidence: 99%
“…However, the low IMF content of yak meat has become a major bottleneck, restricting high-quality meat development in the yak industry. Recent studies report that non-coding RNAs (ncRNAs) regulate key aspects of lipid metabolism [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%